2019
DOI: 10.4143/crt.2017.613
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages Derived TGF-β‒Induced Epithelial to Mesenchymal Transition in Colorectal Cancer Cells through Smad2,3-4/Snail Signaling Pathway

Abstract: Our results demonstrated that TAMs contributed the EMT progression through a TGF-β/Smad2,3-4/Snail signaling pathway, and disrupting this pathway with TGF-β receptor inhibitor could suppress metastasis, readjusting our focus to the connection of TAMs and cancer metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 31 publications
1
77
0
Order By: Relevance
“…As the pivotal factor of the transforming growth factor β pathway, which regulates tumorigenesis and tumor progression, SMAD4 mutations were reported to be present in 2.1%-20.0% of CRC [26]. In a meta-analysis, Huang et al [18] reported that patients with CRC who had a KRAS mutation (combined odds ratio [OR], 1.29; 95% CI, 1.13 to 1.47) or SMAD4 mutation (combined OR, 2.04; 95% CI, 1.41 to 2.95) were at a higher risk of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…As the pivotal factor of the transforming growth factor β pathway, which regulates tumorigenesis and tumor progression, SMAD4 mutations were reported to be present in 2.1%-20.0% of CRC [26]. In a meta-analysis, Huang et al [18] reported that patients with CRC who had a KRAS mutation (combined odds ratio [OR], 1.29; 95% CI, 1.13 to 1.47) or SMAD4 mutation (combined OR, 2.04; 95% CI, 1.41 to 2.95) were at a higher risk of distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We also tested epithelial-mesenchymal transition (EMT)associated protein. In consistent with these results, increased CARD9 was accompanied with decreased N-cadherin and transforming growth factor-!, which were able to facilitate EMT process [12], though E-cadherin and vimentin were unch-anged (Fig. 3C).…”
Section: Table 3 Correlation Between Card9 Expression and The Clinicmentioning
confidence: 99%
“…In our opinion, for one thing, the expression of CARD9 varied in different NSCLC cells, a suggestion of important role of CARD9 within NSCLC cells for tumor development. For another, it is typical of tumor to accumulate myeloid cells [10], such as macrophages [12,20], which should lead to increased CARD9 in vivo. We surmised that dramatical downregulation of CARD9 in NSCLC cells contributed to the decreased CARD9 in vivo, which may play a role in NSCLC development.…”
Section: E C T O R C a R D 9 S H C O N T R O L S H C A R Dmentioning
confidence: 99%
“…One of the main features of tumor cells during tumor progression is their enhanced migration, invasiveness, and angiogenesis through the epithelial-mesenchymal transition (EMT) process. Several lines of evidence have indicated that TAMs are capable of promoting EMT of tumor cells through their secreted factors, including growth factors and cytokines, such as the previously mentioned epidermal growth factor (EGF), and transforming growth factor-β (TGF-β) [52][53][54][55]. Co-culture of M2 macrophages that were polarized from THP1 monocytes with oral cancer or head and neck squamous cancer cells induced the EMT of carcinoma cells through the EGFR pathway and its downstream target ERK in cancer cells [52].…”
Section: Activation Of Cell-stimulating Growth Factors and Cytokinesmentioning
confidence: 99%